Clinical Spectrum of Anterior Scleritis at a Tertiary Eye Care Centre of Western India - Bhole, Pradnya Krishnakant; Gandhi, Kshitij; Parmar, Dipali; Khatri, Resham (Nepalese Journal of Ophthalmology, 2024)
Introduction: Anterior scleritis can be the first sign of an underlying life-threatening systemic disease, can be lethally blinding and its management can be challenging. Thus, it is important to study the clinical spectrum of the disease to aid in early diagnosis and timely management.Objective: To evaluate the clinical spectrum of anterior scleritis (AS) at a tertiary care centre of Western India and to study the importance of its systemic association.Methodology: This analytical cross-sectional (prospective) study was carried out at a tertiary eye care centre of Western India between 2021 February to 2023 January after institutional ethical clearance. A total of 45 eyes of 37 patients were included in the study using convenience sampling.Result: The mean age of presentation was 43.41 ± 14.20 years. The mean follow-up duration was 6.00 ± 5.92 months. Bilateral AS occurred in 21.6% patients and was found to be more common in females (75%). The most common subtype of AS was non-necrotising AS in 35/37 (94.6%) patients. Non-necrotising diffuse AS was more common in females (p=0.047). Systemic association was present in 11/37 (29.73%) patients and rheumatoid arthritis (RA) was the most common systemic condition. Methotrexate was the most common immunosuppressive used in 18.91% patients. The mean time period for recurrence of AS was 3.53 ± 1.35 months. Recurrence was seen in 40.5% patients and was more common in patients with diffuse AS and patients with RA.Conclusion: The RA is an important cause of AS in India and knowledge of the systemic association of AS may enable early diagnosis and timely management of the condition to decrease morbidity and mortality.